Good practice in safeguarding adults: working effectively in adult protection - Pritchard, Jacki (Good practice in health, social care and criminal justice, 2008)
Introduction / Jacki Pritchard -- No secrets, safeguarding adults and adult protection work / Gary Fitzgerald -- Millstone to mainstream: the development of vulnerable adult policy in North Wales / Arwel Wyn Owen -- Two years in the life of an adult protection co-ordinator / Peter Sadler -- Domestic violence and honour based crime: joined up governance and an Islamic approach / Marilyn Mornington -- Elder abuse and black and minorityethnic communities: lessons for good practice / Alison Bowes, Ghizala Avan and Sherry Bien Macintosh -- The role of the Commission for Social Care Inspection / Adrian Hughes -- The abuse in institutions and the resulting inquiries / Deborah Kitson -- Older prisoners in prison: vulnerability, abuse and neglect / Adrian J. Hayes